Developing a Digital Tajwīd E-Booklet to Strengthen Qur’an Literacy for Prospective Couples in Alafan District, Aceh, Indonesia - Vini Nur Zikra (Journal of Social and Community Development, 2026)
This community service program was designed to address the low Qur’an literacy, particularly tajwīd proficiency, among prospective marriage couples (calon pengantin or catin) in Alafan District. Limited learning media, reliance on one-way lecture methods, and the absence of structured tajwīd guidance contributed to inadequate readiness for building an Islamic household. In response, the program developed a practical and accessible Tajwīd E-Booklet that contains essential tajwīd rules, short surahs, supplications, and audio supports. The initiative followed a collaborative and iterative approach involving Sub-District Office of Religious Affairs (Kantor Urusan Agama or KUA) under the Ministry of Religious Affairs of the Republic of Indonesia officers, religious counselors, and the community. The E-Booklet was tested during premarital guidance and received positive feedback from users and facilitators. Results show increased engagement, better accessibility of learning materials, and improved preparation for Qur’an-based family life. This program demonstrates how simple digital innovations can enhance religious literacy, strengthen public services, and uphold the ASN BerAKHLAK values within grassroots community development initiatives.